Improving springboard diving video classification accuracy through cumulated segment values - Bicaj, A.; Meth, H. (Proceedings of the 9th International Performance Analysis Workshop and Conference & 5th IACSS Conference. PACSS 2021, 2022)
Taking the gymnastics games in last five Olympic Games (27th-31th) for instance, this paper uses the methods of literature consultation and mathematical statistics to study the successful experience and sustainable development of Chinese women's gymnastics performance and to summarize the new trends of women's gymnastics games in last five Olympic Games by comparing with the rivals of Chinese women's gymnastics in order to provide a theoretical basis and practical value for the further development of Chinese women's gymnastics.